Apakah Konsumen Menunjukkan Kepercayaan Pada Provider Telkomsel? - Sunarjo, Wenti Ayu; Lukman, Muhammad (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
Currently, cellular network products are widely used by humans in their activities. One of the factors that influence the use of cellular networks is the use of cellular phones and the number of cellular phones used. In addition, because the Telkomsel cellular network has the most users in Indonesia, this can provide an opportunity to increase customer awareness through successful branding. Therefore, the purpose of this study is to see how the variables of brand awareness, brand loyalty, and brand image affect consumer satisfaction. The sample collection technique of 100 respondents used the cluster sampling technique, with questionnaires filled out directly by Telkomsel provider users in Pekalongan City. The results show that brand awareness, brand loyalty, and brand image significantly positively affect consumer trust. However, the limitations of the study which only chose Telkomsel as the provider that was the object of the study need to be carried out in the future by comparing it to other providers to produce comparative data.